Health Education With A Same Age Group - erni chaerani (Poltekkes Kemenkes Pangkalpinang, 2019)
One of the teen reproduce problem especially teen girl is reproduction care. The results of Riskesdas 2013 states that teen’s knowledge about the reproduction health is still low. Some efforts that medical staff could do to resolve the teen reproduction health problem through health education. This research’s aim is to acknowledge the influence of health education with a same age group against teen reproduction health knowledge approach in Pesantren Hidayatussalikin and Nurul Falah. The research plan that use is quantitative analysis with design quasi eksperimen non randomized one group pretest posttest control design to 25 given treatment respondent and 25 control respondent. The result of the research shows mean value of respondent’s knowledge when pretest was 10,34 and post test was 16,02 with p value 0,000. Therefore there is an influence of the health education with a same age group against teen reproduction health knowledge approach. This research’s result may be created as resource material on determining strategy and policy in effort to increase the teen’s knowledge about reproduction health.